Effect of vacuum impregnation with melatonin, γ-aminobutyric acid, and oxalic acid on chilling injury and quality of carambola - Mohd Yusof, Farah Anum; Mohamad Azman, Ezzat; Mohd Adzahan, Noranizan; Yusof, Noor Liyana (Wiley, 2023)
Carambola is a nutrient-rich tropical fruit that ripens and spoils rapidly at ambient temperature, making low-temperature storage a preferable method to address this problem. Unfortunately, carambola suffered a chilling injury when stored at low temperatures. Carambola was vacuum impregnated with melatonin (MT), γ-aminobutyric acid (GABA), and oxalic acid (OA) to mitigate chilling injury and improve its quality during cold storage. Carambola fruits were stored at 4 °C for 28 days and analysed every 7 days. Weight loss, firmness, physicochemical properties, phenolic content, flavonoid content, and proline content were assessed. MT-treated carambola has the highest firmness, 146.31 g and lowest weight loss, 1.53% in comparison to others by the end of the storage period. Visual observations showed that MT-treated carambola ripened evenly, without any chilling injury symptoms and decay was also delayed, whereas OA- and GABA-treated carambola started to decay on day 28. Instead of degrading, phenolics and flavonoids were retained with 6.10% and 12.67% increase when compared to the initial level. GABA-treated carambola can also retain its phenolic and flavonoid content; meanwhile, OA-treated carambola can only retain its phenolic content. Therefore, MT can be applied to mitigate chilling injury and maintain the quality of carambola.